2001
DOI: 10.1038/35077566
|View full text |Cite
|
Sign up to set email alerts
|

Electrical synapses between Gaba-Releasing interneurons

Abstract: Although gap junctions were first demonstrated in the mammalian brain about 30 years ago, the distribution and role of electrical synapses have remained elusive. A series of recent reports has demonstrated that inhibitory interneurons in the cerebral cortex, thalamus, striatum and cerebellum are extensively interconnected by electrical synapses. Investigators have used paired recordings to reveal directly the presence of electrical synapses among identified cell types. These studies indicate that electrical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
319
3
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(336 citation statements)
references
References 62 publications
13
319
3
1
Order By: Relevance
“…Subsequent investigations suggested that gap junction coupling between interneurons (Galarreta and Hestrin, 2001) helps "sharpen" the tuning of γ oscillations, presumably by helping synchronize interneuronal action potentials as the IPSPs wane (Beierlein et al, 2000;Fukuda and Kosaka, 2000;Tamas et al, 2000;Traub et al, 2001a). Fast spiking interneurons do not seem to sustain subthreshold resonance, so intrinsic properties are unlikely to contribute to these kinds of coherent γ oscillation, which argues for a synaptic mechanism (Zemankovics et al, 2010).…”
Section: Network Oscillatorsmentioning
confidence: 99%
“…Subsequent investigations suggested that gap junction coupling between interneurons (Galarreta and Hestrin, 2001) helps "sharpen" the tuning of γ oscillations, presumably by helping synchronize interneuronal action potentials as the IPSPs wane (Beierlein et al, 2000;Fukuda and Kosaka, 2000;Tamas et al, 2000;Traub et al, 2001a). Fast spiking interneurons do not seem to sustain subthreshold resonance, so intrinsic properties are unlikely to contribute to these kinds of coherent γ oscillation, which argues for a synaptic mechanism (Zemankovics et al, 2010).…”
Section: Network Oscillatorsmentioning
confidence: 99%
“…Recent experimental findings suggest that neocortical and hippocampal interneurons innervating the perisomatic region of pyramidal cells coordinate neural oscillatory activity (Fisahn and McBain, 2001;Galarreta and Hestrin, 2001a). Moreover, the synchronous firing of a neural population in the gamma frequency band (30-100 Hz) seems to be associated to cognitive functions (Gray et al, 1989;Csicsvari et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, certain types of neurons (e.g., FS cells Gibson et al 1999;Galarreta and Hestrin 2001 or multipolar bursting Blatow et al 2003 in neocortex) often interact through both electrical and GABAergic synapses. This raises the question of the effect of their combination in neural synchrony.…”
Section: Interplay Between Electrical and Chemical Inhibitory Synapsesmentioning
confidence: 99%
“…This is, for instance, the case in the striatum (Kita et al 1990), the hippocampus (Venence et al 2000), the cerebellum (MannMetzer and Yarom 1999), the reticular thalamic nucleus (Landisman et al 2002), or in the neocortex (Gibson et al 1999;Galarreta and Hestrin 1999;Fukuda and Kosaka 2000). In the neocortex, electrical as well as inhibitory synapses exist between Fast-Spiking (FS) interneurons (Gibson et al 1999;Galarreta and Hestrin 2001) or between Multipolar Bursting neurons (Blatow et al 2003). In contrast, low-threshold-spiking (LTS) interneurons interact mostly via electrical synapses, the inhibitory synapses between them being sparse (Gibson et al 1999;Amitai et al 2002).…”
Section: Introductionmentioning
confidence: 99%